Evolution of distance running shoes: performance, injuries, and rules - Bermon, S. (The Journal of Sports Medicine and Physical Fitness, 2021)
Over the last 50 years, the development of running shoes has been mainly focused on improving the protection and comfort of the runner and her/his foot. Although there have been tentative attempts by companies to make shoes a tool for improving athletic performance, this goal has only recently been achieved. Indeed, the year 2016 was a real turning point when Nike launched its first shoe benefiting from the advanced footwear technology. Advanced footwear technology (AFT) mostly consists of an increased sole thickness, a curved and stiff plate embedded or below the shoe midsole, and an outsole with a marked concave shape. This innovation turned to a game changer in the world of distances running performance. Indeed, between 2016 and 2019, many male and female runners broke personal best times, national records, area, and world records in distance from 5 km to the marathon. The present article aimed at describing the magnitude of these performance enhancements in distance running as well as and the possible underlying performance-enhancement mechanisms associated with the advanced footwear technology. It also reviewed the existing literature on the safety aspects of "classical" construction shoes and AFT shoes. It concluded on a possible shoe mechanical tests-based protocol to maintain fair distance running competitions while not totally preventing manufacturers to innovate, and some thoughts on the nature and goals of further studies to be conducted to assess the safety (macro- and micro-traumatic) AFT in both elite and recreational runner populations.